2017
DOI: 10.1371/journal.pone.0186628
|View full text |Cite
|
Sign up to set email alerts
|

Integrin beta 1 inhibition alleviates the chronic hyperproliferative dermatitis phenotype of SHARPIN-deficient mice

Abstract: SHARPIN (Shank-Associated RH Domain-Interacting Protein) is a component of the linear ubiquitin chain assembly complex (LUBAC), which enhances TNF-induced NF-κB activity. SHARPIN-deficient (Sharpin cpdm/cpdm ) mice display multi-organ inflammation and chronic proliferative dermatitis (cpdm) due to TNF-induced keratinocyte apoptosis. In cells, SHAR-PIN also inhibits integrins independently of LUBAC, but it has remained enigmatic whether elevated integrin activity levels in the dermis of Sharpin cpdm/cpdm mice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Thus, a higher proportion of cell-surface integrins appear to be in an active state in the absence of SHARPIN ( Fig. 2B), in line with our previous studies with MSFs (Peuhu, Kaukonen et al, 2017) and other cell types (Peuhu, Salomaa et al, 2017, Rantala et al, 2011. Next, we analyzed the cell-surface protein levels of integrin β1-binding α-subunits and found that Sharpin cpdm MSFs had slightly downregulated levels of integrin α5, but significantly reduced levels of integrins α1 and α11 on the cell surface compared to wild-type MSFs (Fig.…”
Section: Integrin α111 Protein Levels Regulate the Spreading Of Msfssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, a higher proportion of cell-surface integrins appear to be in an active state in the absence of SHARPIN ( Fig. 2B), in line with our previous studies with MSFs (Peuhu, Kaukonen et al, 2017) and other cell types (Peuhu, Salomaa et al, 2017, Rantala et al, 2011. Next, we analyzed the cell-surface protein levels of integrin β1-binding α-subunits and found that Sharpin cpdm MSFs had slightly downregulated levels of integrin α5, but significantly reduced levels of integrins α1 and α11 on the cell surface compared to wild-type MSFs (Fig.…”
Section: Integrin α111 Protein Levels Regulate the Spreading Of Msfssupporting
confidence: 91%
“…While the role of integrins as cell mechanosensors and transducers is well established, the link between the regulation of integrin activity and the mechanosensing response on different ECM ligands remains poorly understood. SHARPIN is a cytosolic adaptor protein that, among other functions, binds to the intracellular integrin alpha tails and inhibits integrin activity in vitro and in vivo (Peuhu, Kaukonen et al, 2017, Peuhu, Salomaa et al, 2017, Pouwels et al, 2013, Rantala et al, 2011. We have previously demonstrated that stromal SHARPIN deficiency interferes with normal mouse mammary gland development and collagen fiber assembly in vivo (Peuhu, Kaukonen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nonlabeled DOTA-E[c(RGDfK)] 2 peptide and 68 Ga-DOTA-E[c(RGEfK)] 2 peptide significantly reduced the tracer uptake in, for example, small intestine, thus indicating higher level of specific a v b 3 binding in Sharpin cpdm mice than in the wt littermates. In competition experiments, we did not see reduced uptake in the skin of Sharpin cpdm mice, most likely because the skin phenotype is more b 1 integrin-dependent (15). a v b 3 integrin is overexpressed on angiogenic endothelial cells and is a well-validated target for assessing tumor angiogenesis (1).…”
Section: Discussionmentioning
confidence: 98%
“…1A). In these mice, increased integrin activity has been detected in the skin, leukocytes, and mammary gland stromal fibroblasts (12,(15)(16)(17). Although integrins are known to play an important role in tumor growth, invasion, angiogenesis, and metastasis (1), it is currently unclear how regulation of integrin activity in the tumor microenvironment influences these processes.…”
mentioning
confidence: 99%
“…SHANK-associated RH domain interacting protein (SHARPIN) is a ubiquitin-related protein involved in several processes, including inflammatory responses, the development of both normal and cancer tissues [ 69 ], and inhibition of integrin activity in different cell types [ 70 , 71 , 72 , 73 ]. Under physiological conditions, stromal SHARPIN regulates ductal outgrowth during puberty [ 32 ].…”
Section: Mammary Gland Structure and Developmentmentioning
confidence: 99%